A COMPLEX INTERPLAY OF GENES AND BIOLOGICAL PROCESSES UNDERLYING MILK PRODUCTION: REVELATIONS THROUGH GENOME-WIDE ASSOCIATIONS IN SAHIWAL CATTLE - Aneet Kour; S.M. Deb (Journal of Livestock Biodiversity, 2025)
The genetic uniqueness with respect to the performance and sustainability in Bos indicus breeds has been a subject of curiosity for researchers worldwide. Sahiwal is one of these breeds native to Indian-subcontinent which has traversed far and wide around the world due to its superior features. However, the genomic regions and biological processes underlying its production performance have not been studied extensively. We performed a genome-wide association study (GWAS) in the Bos indicus breed Sahiwal to elucidate the genetic architecture of complex milk production traits. Estimated Breeding Values (EBVs) for all eight traits i.e. First lactation 305 days or less milk yield (FL305MY), First lactation average fat percentage (FLAFP), First lactation average protein percentage (FLAPP), First lactation average solid non-fat percentage (FLASNFP), First lactation length (FLL), First lactation average fat yield (FLAFY), First lactation average protein yield (FLAPY), First lactation average solid non-fat yield (FLASNFY). were used as pseudo-phenotype to determine genome-wide associations. In all, 22 SNPs were significantly influencing the traits with the maximum identified for FLL while 3 SNPs were found to be pleiotropic for different traits. On further mapping of these SNPs to the genomic locations, candidate genes affecting the traits were revealed which were associated with diverse range of functions. Further, candidate SNP enrichment was performed to highlight the enriched gene ontology terms and these results also presented a somewhat similar picture with respect to traits being influenced by biological processes underlying a wide spectrum of functions. The findings of this study embolden the point that a complex interplay of biological mechanisms is influencing milk production and further research on this aspect may improvise selection for milk production traits in Sahiwal cattle.